Несет меня лиса: роман / Ирина Богданова - Богданова Ирина Анатольевна (Сибирская Благозвонница, 2020)
Экземпляры: ф.18 (20221221) / Инвентарный номер: 4239 / Цена: / Сис.шифр: 84(2Рос=411.2)6-4 / Авт.знак: Б 73 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6-44